The Effect of Local Coffee Shop Marketing Mix on Customer Satisfaction and Loyalty in Indonesia - Hasbiah, Sitti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
This study aims to analyze the influence of marketing mix factors on customer satisfaction and the subsequent relationship between customer satisfaction and customer loyalty in the context of coffee shops in Makassar. As coffee shops face increasing competition, understanding the dynamics between marketing strategies, customer satisfaction, and loyalty becomes crucial for sustaining growth and achieving differentiation in the marketplace. The research employs multiple regression analysis to evaluate the influence of seven marketing mix elements—product, price, location, promotion, process, physical evidence, and people—on customer satisfaction. Additionally, simple regression analysis is used to assess the impact of customer satisfaction on loyalty. Data for this study are collected through structured questionnaires distributed to coffee shop customers in Makassar. The results reveal that among the seven marketing mix factors, the